Employability and Assessment: How ’blogs’ can diversify the assessment diet and enhance transferable skills - Dixon, Laura (PRISM: Casting New Light on Learning, Theory and Practice, 2023)
Shifts in the Higher Education sector over the past decade have seen greater numbers of applicants than ever before entering university. As undergraduate cohorts have expanded, a diverse student body has emerged, with a rich and complex array of learning needs, desires and expectations. At the same time, public discourse around higher education has changed significantly, and particularly following the introduction and increase of tuition fees, this has led to an emphasis on programmes being seen to provide value for money; a value for money that is being increasingly measured via the metric of graduate employment outcomes. As a result, universities are being pushed to find new ways to ensure that students leave their degree programmes with the kinds of transferable skills necessary to succeed in a contemporary job market that, following shifts in working patterns introduced during the Covid 19 pandemic, values flexibility, and adaptation. This case study – using blogging as a summative assessment at Level 6 of an ‘Events’ Management programme – illustrates that engagement, criticality, and relevance can be successfully incorporated, providing students with a key skill directly relevant to industry.